Curriculum contexts, recontextualisation and attention for higher-order thinking (UCL Press, 2021)
Tasks are crucial for gaining access to powerful knowledge in geography and for fostering higher-order thinking in lessons; therefore, they are key to subject-specific pedagogy. After analysing tasks in geography textbooks for upper secondary education, it was revealed that higher-order thinking barely occurs in textbooks in the Netherlands and is more frequent in North Rhine-Westphalia, Germany. Subsequently, both curriculum contexts were systematically compared to determine factors that influence the use of tasks. The results show that evaluative rules play a crucial role. The assessment in North Rhine-Westphalia focuses on higher-order thinking and how this becomes visible in students' work. Dutch assessment concentrates on students handling an outlined body of knowledge in defined settings. This raises questions of epistemic access, as students are less prepared for the skills expected at university level. Finally, we observed the importance of alignment between official institutions, the discipline of subject-specific pedagogy and support for teachers when it comes to fostering higher-order thinking in geography education.